Absensi PERANCANGAN SISTEM ABSENSI MAHASISWA BERBASIS SMART CARD DAN FINGERPRINT MENGGUNAKAN FRAMEWORK ITIL - Indra Dharma Wijaya, S.T., M.MT.; Aisha Rahmadia Aqilah; Prihandiva, Fitria Ramadhani; Naura Haidar Ramadhona Arzin (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Recording student attendance at higher education is an important aspect in managing the learning process. The paper-based attendance system at the Malang State Polytechnic Information Technology Department faces serious challenges, including potential damage, risk of data corruption, and efficiency failures. A survey in November 2023 revealed absenteeism by some students, highlighting weaknesses in the system. This research aims to improve the accuracy of the attendance system, strengthen trust in attendance data, and provide technology-based solutions. The methods used are quantitative and qualitative, with questionnaires and observations of students. The research results are expected to provide a basis for improving policies and implementation of the attendance system, minimizing conditions, increasing efficiency, and strengthening student attendance management in the Information Technology Department.